A Rapid and Facile Purification Method for Glycan‐Binding Proteins and Glycoproteins. (3rd September 2020) - Welch, Christina J.; Kadav, Priyanka D.; Edwards, Jared L.; Krycia, Jessica; Talaga, Melanie L.; Bandyopadhyay, Purnima; Dam, Tarun K.
Abstract: Glycosylated proteins, namely glycoproteins and proteoglycans (collectively called glycoconjugates), are indispensable in a variety of biological processes. The functions of many glycoconjugates are regulated by their interactions with another group of proteins known as lectins. In order to understand the biological functions of lectins and their glycosylated binding partners, one must obtain these proteins in pure form. The conventional protein purification methods often require long times, elaborate infrastructure, costly reagents, and large sample volumes. To minimize some of these problems, we recently developed and validated a new method termed capture and release (CaRe). This method is time‐saving, precise, inexpensive, and it needs a relatively small sample volume. In this approach, targets (lectins and glycoproteins) are captured in solution by multivalent ligands called target capturing agents (TCAs). The captured targets are then released and separated from their TCAs to obtain purified targets. Application of the CaRe method could play an important role in discovering new lectins and glycoconjugates. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of crude extracts containing the target proteins from soybean flour Alternate Protocol 1 : Preparation of crude extracts from Jack bean meal Alternate Protocol 2 : Preparation of crude extracts from the corms of Colocasia esculenta, Xanthosoma sagittifolium, and from the bulbs of Allium sativum Alternate Protocol 3 : Preparation of Escherichia coli cell lysates containing human galectin‐3 Alternate Protocol 4 : Preparation of crude extracts from chicken egg whites (source of ovalbumin) Basic Protocol 2 : Preparation of 2% (v/v) red blood cell suspension Basic Protocol 3 : Detection of lectin activity of the crude extracts Basic Protocol 4 : Identification of multivalent inhibitors as target capturing agents by hemagglutination inhibition assays Basic Protocol 5 : Testing the capturing abilities of target capturing agents by precipitation/turbidity assays Basic Protocol 6 : Capturing of targets (lectins and glycoproteins) in the crude extracts by target capturing agents and separation of the target‐TCA complex from other components of the crude extracts Basic Protocol 7 : Releasing the captured targets (lectins and glycoproteins) by dissolving the complex Basic Protocol 8 : Separation of the targets (lectins and glycoproteins) from their respective target capturing agents Basic Protocol 9 : Verification of the purity of the isolated targets (lectins or glycoproteins)